2002
DOI: 10.1063/1.1465406
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical characterization of the lowest-energy absorption band of pyrrole

Abstract: The lowest-energy band of the electronic spectrum of pyrrole has been studied with vibrational resolution by using multiconfigurational second-order perturbation theory ͑CASPT2͒ and its multistate extension ͑MS-CASPT2͒ in conjunction with large atomic natural orbital-type basis sets including Rydberg functions. The obtained results provide a consistent picture of the recorded spectrum in the energy region 5.5-6.5 eV and confirm that the bulk of the intensity of the band arises from a * intravalence transition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
145
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(163 citation statements)
references
References 40 publications
17
145
1
Order By: Relevance
“…Thus the error in the excitation energies of neutral species must be in the TDHF method. A literature search for benchmark calculations revealed that high-level ab initio calculations are published only for pyrrole [93][94][95][96] and not for longer oligomers. The best estimate at the coupledcluster level for the π-π* transition of pyrrole, 6.57 eV, is even higher than our TDHF value of 6.47 eV.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the error in the excitation energies of neutral species must be in the TDHF method. A literature search for benchmark calculations revealed that high-level ab initio calculations are published only for pyrrole [93][94][95][96] and not for longer oligomers. The best estimate at the coupledcluster level for the π-π* transition of pyrrole, 6.57 eV, is even higher than our TDHF value of 6.47 eV.…”
Section: Discussionmentioning
confidence: 99%
“…Already with the triple-basis set, the CASPT2-F12 dissociation energy is within 0.5 kcal/mol of the CBS limit. In contrast, the basisset truncation error of the conventional CASPT2 method amounts about 3 and 1.3 kcal/mol with the triple-and 36,37 does not appear with this relatively small CAS. In order to describe the Rydberg states properly, the cc-pVXZ-F12 basis sets of C and N have been augmented by one even-tempered diffuse p function 23 ͑denoted as VXZ-F12+ in Table III͒.…”
mentioning
confidence: 83%
“…19 According to the calculation result, 17 the only accessible electronic state was 1B 2 (5.99 eV, π(a 2 ) f π*(b 1 )). The contribution of the 1B 2 (ππ*) valence excited state to the lowestenergy absorption band was 1 order of magnitude larger than that of the other excited states, such as 2A 1 (ππ*), 1B 1 (3p y ) and 2B 2 (3p x ).…”
Section: ' Results and Discussionmentioning
confidence: 95%
“…The other two states, 1A 2 (3s) and 2A 2 (3p z ), were dipoleforbidden. 19,20 Transition to the 1B 1 (3p y ) and 2B 2 (3p x ) Rydberg state might also contribute to the absorption band. 21 The absorption band to the 1B 2 (ππ*) state displayed a large number of vibrational progressions.…”
Section: ' Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation